Estudo para implantação do Manufacturing Execution System (MES) em uma fábrica de injeção plástica - Andreazza, Luan Michel (My University, 2020)
The MES - Manufacturing Execution System is a tool to controlling production applied on the factory floor that allows you to view and monitor processes on-line, providing information seeking operational gain. This article presents a study carried out in a plastic injection sector in a household appliance company. It aims to map of implementing the MES system and how the insertion of this technology favors production management, creating a remote control of production and facility for generating performance reports, aiming at increasing performance, reducing costs and reducing lead times. This work also compares the current data collection model (ERP and spreadsheets) with the MES system, as well as the gains in the production process, in addition to budgets, deadlines and matrix for decision making. The information used to support the implementation study was collected through a theoretical framework, studies carried out by the multifunctional team responsible for the project, in addition to visits and budgets with possible information system suppliers and presented consistent results for the implementation of the project in the organization. [resumo fornecido pelo autor]
O Manufacturing Execution System (MES ? Sistema de Execução da Manufatura) é uma ferramenta para controle da produção aplicada no chão de fábrica que permite visualizar e monitorar processos de forma on-line, fornecendo informações que visam ganho operacional. Este artigo apresenta um estudo realizado no setor de injeção plástica em uma empresa de utensílios domésticos. Possui objetivo de mapear a implantação do sistema MES e como a inserção dessa tecnologia favorece a gestão da produção, criando um controle remoto da produção e facilidade para geração de relatórios de desempenho, visando aumento de desempenho, redução de custos e redução de lead times. Este trabalho também compara o modelo atual de coleta de dados (ERP e planilhas eletrônicas) com o sistema MES, bem como os ganhos no processo produtivo, além de orçamentos, prazos e matriz para tomada de decisão. As informações empregadas no embasamento do estudo de implantação foram coletadas por meio de referencial teórico, estudos realizados pela equipe multifuncional responsável pelo projeto, além de visitas e orçamentos com possíveis fornecedores de sistemas de informações e apresentaram resultados consistentes para a implantação do projeto na organização. [resumo fornecido pelo autor]
Keywords: Manufacturing Execution Systems; Engenharia de produção